Risk analysis of human-wildlife conflict in Leuser Ecosystem Area, Indonesia - IRWANDI IRWANDI; ABDUL RAUF; RAHMAWATY RAHMAWATY; DELVIAN DELVIAN; R. HAMDANI HARAHAP; AGUS PURWOKO (Society for Indonesian Biodiversity, 2026)
Abstract. Irwandi, Rauf A, Rahmawaty, Delvian, Hamdani, Purwoko A. 2026. Risk analysis of human-wildlife conflict in Leuser Ecosystem Area, Indonesia. Biodiversitas 27 (1): d270120. https://doi.org/10.13057/biodiv/d270120. Over the past six years, the Aceh Natural Resources Conservation Agency recorded 542 incidents of human-elephant conflict. In 2023 alone, 13 farmers and residents were attacked by wild tigers and elephants, resulting in injuries and fatalities. Additionally, at least 19 tigers died in Aceh between 2019 and 2022. This study aims to assess the risk of wildlife conflict to community livelihoods in seven villages within the Leuser Ecosystem Area. A mixed-methods approach was employed, combining quantitative and descriptive qualitative methods. Data collection involved the distribution of questionnaires covering 10% of households from the total population. The combined population of the seven surveyed villages is 2,673 households, from which 268 households (10%) were sampled using proportionate random sampling based on population size in each village. In addition to questionnaires, the study also conducted Focus Group Discussions (FGDs). In addition to questionnaires, the study also conducted Focus Group Discussions (FGDs). These were designed to validate survey findings and capture deeper community perspectives on risk perception, conflict experiences, and local coping strategies. Data analysis followed the Miles and Huberman model, consisting of three stages: data reduction, data display, and conclusion drawing. The study found that the perceived risk of wildlife conflict to livelihoods was generally low. However, some villages reported a medium level of risk. Most villages exhibited moderate vulnerability, with significant variation across dimensions of human, social, economic, physical, and environmental vulnerability. From a risk assessment perspective, the combination of low vulnerability and low threat levels contributes to a low overall risk of wildlife conflict for local government.